2018
DOI: 10.1016/j.tcs.2017.12.032
|View full text |Cite
|
Sign up to set email alerts
|

Exact learning of juntas from membership queries

Abstract: In this paper we study adaptive and non-adaptive exact learning of Juntas from membership queries. We use new techniques to find new bounds, narrow some of the gaps between the lower bounds and upper bounds and find new deterministic and randomized algorithms with small query and time complexities.Some of the bounds are tight in the sense that finding better ones either gives a breakthrough result in some long-standing combinatorial open problem or needs a new technique that is beyond the existing ones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 37 publications
(119 reference statements)
0
6
0
Order By: Relevance
“…Therefore the class d-Junta is almost optimally learnable. Bshouty and Costa, [49], close the above gap and showed that OPT NAD (d-Junta) = O(d2 d log n).…”
Section: D-xormentioning
confidence: 79%
See 3 more Smart Citations
“…Therefore the class d-Junta is almost optimally learnable. Bshouty and Costa, [49], close the above gap and showed that OPT NAD (d-Junta) = O(d2 d log n).…”
Section: D-xormentioning
confidence: 79%
“…A better query complexity can be obtained from the reduction in [49]. See the following Table. The outputs of the above algorithms are the Fourier representation of the decision tree and, therefore, they are non-proper learning algorithms.…”
Section: Non-adaptive Learning Decision Treementioning
confidence: 99%
See 2 more Smart Citations
“…We develop effective construction techniques for combinatorial arrays called covering perfect hash families, which form a compact representation of covering arrays. Covering arrays arise in numerous applications in which interactions among options or factors are to be measured; they are used in, for example, software testing [12,13], hardware testing [10,20], design of composite materials [2], computational learning [1,9], and biological networks [14]. Computational methods to construct covering arrays often encounter difficulties when the array has many rows, many columns, or both.…”
Section: Introductionmentioning
confidence: 99%